Mould making - Colclough, John (Craftsman House, 1999)
"Mould making used to be thought of as primarily an industrial technique. However, today, artists in many fields are finding it a useful tool in realising their creative vision. In this book, John Colclough carefully expalins how to successfully make and use moulds of varying complexities, both for industrial and artistic use. This book should be a must for anyone venturing into this field." -- Provided by publisher